2014
DOI: 10.1111/jpc.12712
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of human immunodeficiency virus‐infected children after anti‐retroviral therapy in Malaysia

Abstract: Aims To describe outcome and examine factors associated with mortality among human immunodeficiency virus (HIV)-infected children in Malaysia after anti-retroviral therapy (ART). Methods Retrospective and prospective data collected through March 2009 from children in four different states in Malaysia enrolled in TREAT Asia’s Pediatric HIV Observational Database were analysed. Results Of 347 children in the cohort, only 278 (80.1%) were commenced on ART. The median CD4 count and median age at baseline prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
3
5
2
Order By: Relevance
“…Children, who had CD4 counts or percents below the threshold, yet another strong predictor of mortality, showed a higher risk of death than their counterparts. This finding is consistent with other previous studies conducted in Ethiopia [ 1 , 17 , 23 ], India [ 32 ], Congo [ 33 ], Tanzania [ 31 ], Bangladesh [ 34 ] and Malaysia [ 35 ]which all indicate that low CD4 count was an independent predictor of mortality. Children with severe immunodeficiency are at higher risk of developing serious and life-threatening opportunistic infections, such as CNS toxoplasmosis and cryptococcal meningitis.…”
Section: Discussionsupporting
confidence: 93%
“…Children, who had CD4 counts or percents below the threshold, yet another strong predictor of mortality, showed a higher risk of death than their counterparts. This finding is consistent with other previous studies conducted in Ethiopia [ 1 , 17 , 23 ], India [ 32 ], Congo [ 33 ], Tanzania [ 31 ], Bangladesh [ 34 ] and Malaysia [ 35 ]which all indicate that low CD4 count was an independent predictor of mortality. Children with severe immunodeficiency are at higher risk of developing serious and life-threatening opportunistic infections, such as CNS toxoplasmosis and cryptococcal meningitis.…”
Section: Discussionsupporting
confidence: 93%
“…The mortality rate in our study is lower than the rates of 2.25, 3.0 4.0, 4.7, and 8.4 per 100 child-years reported in Malawi, Lesotho, and Swaziland, 30 in Nigeria, 31 in Ethiopia, 27 in South Africa, 25 and in Kenya, 32 respectively. It is also lower than the rate in other reports from in Asian countries such as China (2.31 per 100 child-years), 9 Malaysia (2.86 per 100 child-years) 8 and India (4.4–4.9 per 100 person-years). 10 The outcome of this study is similar to that of Lumbiganon et al 7 who studied 2280 children in 5 countries in the Asia-Pacific region, including Vietnam.…”
Section: Discussioncontrasting
confidence: 60%
“…ART programs for HIV-infected children in Asian countries have been shown to be effective, with mortality rates ranging from 1.9 child-years to 4.9 child-years. [7][8][9][10][11] The common risk factors for mortality were a low CD4 percentage, WHO clinical stage 3 or 4 and malnutrition. [8][9][10]12 In a cohort of 266 HIV-infected children with suspected tuberculosis (TB) in four countries (Burkina Faso, Cambodia, Cameroon, and Vietnam), Marcy et al found that TB, young age, CD4 less than 10%, miliary features, and elevated serum transaminases were all independent predictors of mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, a Brazilian study also reported that baseline CD4 count below 15% significantly increased the hazard of death among HIV-positive children [ 33 ]. Similarly, studies conducted elsewhere have documented that HIV-positive children with low CD4 count were at higher risk of mortality than those who had high CD4 count [ 28 , 34 36 ]. Generally, serious and life-threatening OIs, including CNS toxoplasmosis and cryptococcal meningitis are frequent among people having low CD4 count or percentages which increases their vulnerability to death.…”
Section: Discussionmentioning
confidence: 98%